Writing like a flock. - Conley, D.S. (Social Identities, 2009)
Theories and practices of self-organization have spread broadly in recent decades, through academia to business management to software development to disaster relief planning to progressive political activism, and so on. The question this paper addresses is whether self-organization can also become a viable mode of cultural analysis. Using the experience of January 2007, when a varied group of scholars convened in Las Vegas to 'swarm' the Consumer Electronics Show, I examine in detail this question of swarm-as-method. The 'swarm scholarship' we road-tested at the convention is suggestive on a number of levels, but foremost for the way it challenges fundamental norms and expectations surrounding authorship. A mode of scholarship such as our swarm stands little chance in the University, I argue, because it requires a different environment of rewards and incentives than currently dominant in the research culture of academia.